2021
DOI: 10.1108/ecam-02-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

How perceived corporate social responsibility and public knowledge affect public participation intention: evidence from Chinese waste incineration power projects

Abstract: PurposePublic participation is essential for mitigating local resistance faced by the environmentally stigmatized facilities. The purpose of this study is to investigate public participation intention in the decision-making of waste incineration power (WIP) projects by examining the role of perceived corporate social responsibility (PCSR) and public knowledge (PK) based on the theory of planned behavior (TPB).Design/methodology/approachA theoretical model correlating PCSR with public participation intention wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…In this study, PBC means that the public has time, money and ability to pay for their healthy housing. In other words, the more the public can control the above mentioned factors, the more the behavioral intention will be conducted ( 42 ). As such, the following hypothesis is proposed in this study:…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In this study, PBC means that the public has time, money and ability to pay for their healthy housing. In other words, the more the public can control the above mentioned factors, the more the behavioral intention will be conducted ( 42 ). As such, the following hypothesis is proposed in this study:…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The essence of residents’ responsibility cognition is to recognize the significance and value of environmental governance behavior, enhance their self-efficacy and stimulate their initiative. The government’s environmental governance publicity can also enhance rural residents’ awareness of responsibility, sense of responsibility and mission and encourage individuals to take the initiative to take responsibility and fulfill their environmental governance responsibilities [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2020) proposed that consumer perceived CSR image can enhance consumers' identification with companies and their environmental responsibilities, promote their participation in sustainable environmental behavior, and trigger citizenship behaviors such as recommendation and advocacy. Based on the reciprocity perspective, Wan et al. (2021) suggested that environmentally responsible corporate behavior and individual proenvironmental behavior comprise a type of resource swap.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Accordingly, CSR image started to receive more attention during and after COVID-19 (V at am anescu et al, 2021; He and Harris, 2020). In the field of proenvironmental behavior, studies have verified the promotion effect of CSR image on individuals' proenvironmental behavior, mainly from the perspectives of identity and reciprocity (Curras-Perez et al, 2018;Dang et al, 2020;Chuah et al, 2020;Wan et al, 2021). Based on the identity perspective, Dang et al (2020) suggested that when consumers have a high perceived CSR image, they will believe that companies will engage in business activities that protect the environment and benefit consumers.…”
Section: Moderating Effect Of Perceived Csr Imagementioning
confidence: 99%